Princess in pink - Cabot, Meg ([New York] HarperCollins Publishers, 2004)
In a series of humorous diary entries, high school freshman (and Genovian Princess) Mia tries to get her reluctant boyfriend to take her to the prom
Age 12+
Grade 7+
1
NEW, LITERATURE
Keywords: Diaries -- Fiction; High schools -- Fiction; Humorous stories; Princesses -- Fiction; Proms -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction